Teaching and Learning Guide for: Sacred Space in the Ancient Near East - Wasilewska, Ewa (Religion compass, 2010)
This guide accompanies the following article: Ewa Wasilewska, Sacred Space in the Ancient Near East, Religion Compass 3/3 (2009) pp. 395-416, 10.1111/j.1749-8171.2009.00138.x Author’s Introduction Although the topic of sacred spaces in the Near East is an interesting one, it is also quite challenging to teach. The amount of available data regarding discoveries of sacral enclosures in the area is enormous. The complexity in methodological issues encompasses many disciplines of social sciences and humanities. Thus, any instructor who attempts such a task must make his/her own choices as to the leading themes and/or areas that shall be covered in a course. The following is just a suggestion of basic sources that may make a personal selection of both literature and topics easier for an instructor. General Reading List This list focuses on basic sources intended to provide background information about archeology and the ancient Near East in general. More sources are listed under specific topics of the proposed syllabus. Introduction to archeology Chazan, M. World Prehistory and Archaeology: Pathways through Time. Boston: Pearson Education, Inc. 2008. This is a comprehensive and thoughtful introduction to methods and theories in modern archeology. Although examples used are not only from the Near East, the strong point of this introduction is its organization that includes summaries of key points, review questions, and recommendations for further readings. Introduction to anthropology of religion Crapo, R. H. Anthropology of Religion: The Unity and Diversity of Religions. McGraw Hill. 2002. As a basic source of information on anthropology of religion this book is quite sufficient. However, it is recommended that, if possible, various Readers in Anthropology of Religion might be used as supplemental readings. Introduction to ancient sacred spaces Wightman, G. J. Sacred Spaces: Religious Architecture in the Ancient World. Leuven: Peeters. 2007. This book is a comprehensive introduction to the most famous sacred spaces of the ancient world. However, the reader must be warned that due to the wealth of information (different civilizations, different time periods) presented, this book is somewhat uneven. Introduction to archeology of Mesopotamia Matthews, R. The Archaeology of Mesopotamia. Theories and Approaches. London and New York: Routledge. 2003. Roaf, M. Cultural Atlas of Mesopotamia and the Ancient Near East. Oxford: Andromeda Oxford Limited. 2002. These books are excellent introductions to the region, both from the descriptive and methodological points of view. Mieroop, M. Van De. A History of the Ancient Near East ca. 3000-323 B.C. Blackwell Publishing. 2007. Mieroop’s works provides a very valuable source on the ancient Near East while combining archeological data with available written records. Introduction to archeology of Egypt Bard, K. An Introduction to the Archaeology of Ancient Egypt. Blackwell Publishing. 2008. This is the most comprehensive and updated book on archeology of Egypt. Wilkinson, R. H. Egyptology Today. Cambridge University Press. 2008. This is a valuable collection of articles written by leading Egyptologists who focus on variety of methodological and theoretical issues in modern Egyptology. Introduction to archeology of Anatolia (mostly Hittite period) Bryce, T. Life and Society in the Hittite World. Oxford University Press. 2002. Macqueen, J. G. The Hittites and Their Contemporaries in Asia Minor. Thames & Hudson. 2003. Both books are basics for learning about Anatolia of the second millennium B.C. Introduction to archeology of Levant (Syria Palestine) Akkermans, M. M. G. & Schwartz, G. M. The Archaeology of Syria. From Complex Hunter-Gatherers to Early Urban Societies (ca. 16,000-300 B.C.). Cambridge University Press. 2003. This is the only comprehensive source of knowledge on archeology of Syria focusing on archeological data and their interpretation. Introduction to archeology of Iran Curtis, J. E. and N. Tallis, eds. Forgotten Empire: The World of Ancient Persia. University of California Press. 2005. Potts, D. T. The Archaeology of Elam: Formation and Transformation of an Ancient Iranian State. Cambridge University Press. 1999. These two books focus on different periods in the history of Iranian civilizations. While the first one combines both archeology and historical sources to provide a comprehensive discussion of the Persian empire, the second one utilizes mostly archeological data. General introduction to cosmology of the ancient Near East Clifford, R. Creation Accounts in the Ancient Near East and in the Bible. The Catholic Biblical Quarterly Monograph Series, 26. Washington, DC: The Catholic Biblical Association of America, 1994. or Wasilewska, E. Creation Stories of the Middle East. London and Philadelphia: Jessica Kingsley Publishers. 2000. While the choice of creation accounts in both books is very similar, the first book’s approach is more theological than of the second one that focuses on evolution of different concepts. Sample Syllabus This sample syllabus includes sample readings appropriate to students at different levels: introductory, advanced, and, at occasions, general audience interest. While whole books are often recommended, the selection of relevant chapters is left to an instructor to focus on issues that he/she finds most valuable for addressing the topic of sacred space in the ancient Near East. 1. Welcome to the Past: A Brief Introduction to History of Archeology and Its Methods and Theories Focus: The topic of sacred spaces in the ancient Near East cannot be fully discussed without understanding limitations archeological and historical data present for recognition and interpretation of ancient beliefs. Introductory level Chazan, M. World Prehistory and Archaeology: Pathways through Time. Boston: Pearson Education, Inc. 2008. Advanced level Hodder, I. & Hutson, S. Reading the Past. Current Approaches to Interpretation in Archaeology. Cambridge University Press. 2003. Third edition. Recommended for general audience Balter, M. The Goddess and the Bull. Çatal Hüyük: An Archaeological Journey to the Dawn of Civilization. New York: Free Press. 2005. This is a fascinating book written in an excellent journalistic style introducing a reader not only to one of the most famous sites of the Near East, Çatal Hüyük, but also personalizing archeological disputes regarding both excavating, reporting, and interpreting the past. 2. Anthropology and Archeology of Religion Focus: This discussion shall focus on introducing students to the variety of approaches in understanding and researching such concepts as ‘religion,’‘sacral space,’‘sacred vs. profane,’ etc. Introductory level Crapo, R. H. Anthropology of Religion: The Unity and Diversity of Religions. McGraw Hill. 2002. Insoll, T. Archaeology, Ritual, Religion. Routledge Press. 2004. Advanced level Durkheim, E. The Elementary Forms of the Religious Life. London: George Allen &Linwin Ltd. 1954. Eliade, M. The Sacred Space and the Profane: The Nature of Religion. New York: Harper & Row, Publishers. 1959. Recommended for general audience Website: Understanding the Sacred. http://www.bytrent.demon.co.uk/eliadesp01.html. An interesting website that presents, summarizes, and discusses various approaches to understanding of the sacred. 3. First was the temple, then was the food…? The Neolithic Period and its sacral places Focus: The transition from food gathering to food producing economies in the Neolithic Period has likely resulted in changes in ideological systems and selections as well as character of sacred spaces. ‘Is such a change reflected in archeological material’ becomes then a quite challenging question to modern archeologists. Introductory level Cauvin, J. The Birth of the Gods and the Origins of Agriculture. Cambridge University Press. 2003. This is quite a controversial book that challenges conventional approaches to the understanding of the beginnings of agriculture and domestication of animals in the ancient Near East. Curry, A. ‘Göbekli Tepe: The World’s First Temple?’ In Smithsonian Magazine. November 2008. Electronic version at http://www.smithsonianmag.com/history-archaeology/gobekli-tepe.html. or Scham, S. ‘The World’s First Temple.’ In Archaeology 61-6. 2008. Pp. 22-7. Advanced level Matthews, R. ‘Chapter 3. Tracking a transition: Hunters becoming farmers.’ In The Archaeology of Mesopotamia. Theories and Approaches. London & New York: Routledge. 2003. Pp. 67-92. Kuijit, I. and M. S. Chesson: ‘Lumps of Clay and Pieces of Stone: Ambiguity, Bodies, and Identity as Portrayed in Neolithic Figurines.’ In S. Pollock and R. Bernbeck eds., Archaeologies of the Middle East. Critical Perspectives. Blackwell Publishing. 2005. Pp. 152-83. This chapter demonstrates challenges and ‘options’ in interpreting figural representations of the Neolithic Period. 4. The temple and the state: temples as centers of collection and redistribution of wea ...